Peningkatan Kemampuan Guru Madrasah Tsanawiyah Dalam Menyusun RPP di Masa Pandemi Covid-19 Melalui in House Training (iHT) - Arifin, Widad (Nusantara: Jurnal Pendidikan Indonesia, 2021)
This research is a Surveillance Action Research (PTKp) with four main steps, namely: action planning, action implementation, observation and reflexes. The research subjects were 8 teachers at Madrasah Tsanawiyah Negeri 2 Sukabumi consisting of 6 classroom teachers and 2 subject teachers. It can be concluded that the application of iHT with the Google Meeting Application has proven to be able to improve the ability of teachers in preparing lesson plans during the Covid 19 pandemic. The average score for the LESS criteria in the initial state is 49.44, increasing to 70.83 for the ENOUGH criteria in cycle I and 90.56 for GOOD criteria in the second cycle. Regarding the capacity of teachers at Madrasah Tsanawiyah Negeri 2 Sukabumi in preparing individual lesson plans during the Covid 19 pandemic, in the initial conditions no teachers were declared complete, but in cycle 1 five teachers (55.56 percent) were declared complete, and nine teachers (100 percent) is declared complete in cycle 2.